The Consumers’ Perception and Frequency of Visit Before and After Wet Market Revitalization (Jurnal Bina Praja, 2018)
The Ministry of Trade revealed that there are 41 wet markets in 12 provinces in Indonesia suffering from damage, 50 percent of which are due to incomplete and inadequate market facilities. From a survey of 3,956 markets, 95 percent of them have a physical building over 25 years. In Banyumas regency there are two wet markets that have experienced the revitalization program, namely those in Cilongok and Sokaraja. However, this research focused on Cilongok market. This research aims to compare consumer assessment toward the level of cleanliness, safety, orderliness, and lighting, level of favorability and frequency of consumer visit to Cilongokwetmarket. This study used a comparative descriptive method to compare consumers’ assessment. The before-after approach is used to assess the effectiveness of the treatment, characterized by an average difference before and after treatment. This research surveyed 100 respondents selected by accidental sampling. Data were collected by questionnaire-based exit interview. Data of the assessment pre-revitalization are obtained by recall method. Data were then analyzed using paired sample t-test. The results show that consumer assessment toward the level of cleanliness, safety, orderliness, and lighting of the Cilongokwet market after revitalization is higher than that before revitalization. Moreover, their level of favorability and frequency of visiting the market are higher, too. The results imply that revitalization of wet markets has been perceived positively by consumers, which has affected their frequency of shopping, thereby improving the competitiveness of the wet market against the modern market.
Keywords: Wet Market; Consumer Behavior; Revitalization; Consumer Perception